N-SIPPV versus bi-level N-CPAP for early treatment of respiratory distress syndrome in preterm infants. (17th April 2013) - Ricotti, Alberto; Salvo, Vincenzo; Zimmermann, Luc J. I.; Gavilanes, Antonio W. D.; Barberi, Ignazio; Lista, Gianluca; Colivicchi, Micaela; Temporini, Francesca; Gazzolo, Diego
Abstract: Objective : Non-invasive ventilation (NIV) for RDS in extremely/very low birth-weight infants represents the new challenge for neonatologists. In this regard, data comparing the effectiveness of Bi-Level-NCPAP (BiPAP) versus nasal synchronized intermittent positive pressure ventilation (NSIPPV) as primary mode of treatment for RDS are lacking. Study design : We conducted a retrospective study from December 2007 to December 2010 in seventy-eight infants, who received NIV (N-SIPPV: 33; BiPAP: 45). The primary outcomes were the length and failure of NIV. Secondary outcomes were adverse short-long term pulmonary outcomes, multiple doses of surfactant and others. Results : There were no significant differences ( p  > 0.05) between the two different NIV modes. Conclusion : The present findings suggest that N-SIPPV and BiPAP gives similar results in the RDS treatment. We did not find a benefit of one over the other ventilation mode and both could be constitute a valid option to conventional mechanical ventilation. The theoretical benefits of these two different methods of NIV are tidal volume enhancement, improvements of the functional residual capacity and of the mean airway pressure and reducing apnea episodes. Further randomized studies to assess the advantages and the efficacy of different methods of NIV for the treatment of the RDS are needed.